2014 IEEE International Symposium on Broadband Multimedia Systems and Broadcasting 2014
DOI: 10.1109/bmsb.2014.6873572
|View full text |Cite
|
Sign up to set email alerts
|

A novel methodology for mapping objective video quality metrics to the subjective MOS scale

Abstract: Abstract-With the rapid growth in video-based services, and as users are becoming increasingly quality-aware, the reliable estimation of video quality has become extremely important. While a multitude of objective Video Quality Assessment (VQA) metrics with various performance and complexity have been proposed, the nonlinearity of video quality and the lack of clear interpretations of the metrics make difficult to understand how the objective metric values reflect the video quality as perceived subjectively in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Table 3 summarizes the PSNR and SSIM results of the proposed and reference methods; these results provide the average values for 100 intensity images that were numerically obtained. The PSNR and SSIM of the proposed method are less than those of the reference method; however, they exceeds the standard of fair quality images (PSNR is 25 dB and SSIM is 0.88 higher) [32]. Thus, from the quantitative results, we confirmed that the proposed method can reconstruct the 3D images with sufficient image quality.…”
Section: B Image Qualitysupporting
confidence: 52%
“…Table 3 summarizes the PSNR and SSIM results of the proposed and reference methods; these results provide the average values for 100 intensity images that were numerically obtained. The PSNR and SSIM of the proposed method are less than those of the reference method; however, they exceeds the standard of fair quality images (PSNR is 25 dB and SSIM is 0.88 higher) [32]. Thus, from the quantitative results, we confirmed that the proposed method can reconstruct the 3D images with sufficient image quality.…”
Section: B Image Qualitysupporting
confidence: 52%
“…This paper extends our preliminary work [14] with a detailed description of the VQAMap mechanism as well as a comprehensive evaluation conducted on data from three public databases (i.e., ECVQ, EVVQ and LIVEM). The paper also illustrates how VQAMap can be used to create mapping rules for six different full-reference metrics (i.e., PSNR, 0018-9316 c 2016 IEEE.…”
Section: Introductionmentioning
confidence: 98%
“…Users are exposed to distorted videos and through this process a mean opinion score (MOS) is derived [19]. Although subjective methods are the most accurate way for VQA [20], they require resources and are time-consuming. This is the reason why objective methods are more attractive to researchers and a lot of work has been done towards developing objective quality metrics [21].…”
Section: Introductionmentioning
confidence: 99%